SEASONAL AND GEOGRAPHICAL ANALYSIS OF AFLATOXINS IN DIFFERENT VARIETIES OF PAKISTANI BROWN RICE - Muhammad Kashif; Muhammad Riaz; Saeed Akhtar; Khurram Muaz; Habibullah Nadeem; Shinawar Waseem Ali; Amir Ismail (Journal of Animal and Plant Sciences, 2024)
Aflatoxins are highly toxic, carcinogenic compounds, widely prevalent worldwide, secreted by various fungal strains especially from genus Aspergillus including Aspergillus parasiticus and Aspergillus flavus. Brown rice having more than 17% moisture contents is considered as favorable substrates for fungal growth causing aflatoxins production. The objective of current study was to examine seasonal and geographical impact on production of aflatoxins including aflatoxin B1 (AFB1), aflatoxin B2 (AFB2), aflatoxin G1 (AFG1) and aflatoxin G2 (AFG2) in different brown rice varieties procured from various regions of Punjab and Sindh. High Performance Liquid Chromatography (HPLC) equipped with fluorescence detector was used to detect aflatoxins in samples including Super Kernel Basmati Rice, Kainat, Supri, Super Sindh, IRRI-6 and IRRI-9 hybrid. Among aflatoxins, AFB1 was the most common toxin detected in several varieties of Pakistani brown rice especially in Super Kernel Basmati Rice and in Super Sindh. Total 202 (50.5%) out of 400 samples were contaminated with aflatoxins out of which 135 samples (33.75%) had AFB1 level exceeding permissible limit (2 µg/kg). In addition, 125 (31.25%) samples had higher total aflatoxins contents than allowable limit (4 µg/kg). AFG1 and AFG2 in present study were not detected. Aflatoxins concentrations in brown rice varieties collected from Punjab were higher than those collected from Sindh province. The seasonal comparison for aflatoxins concentrations in brown rice showed higher aflatoxins levels in the samples collected during the month of March than those procured in other months (November, January and May). Furthermore, a strong correlation between moisture contents and aflatoxins was also observed. The results indicated that aflatoxins contents in various Pakistani brown rice varieties cannot be ignored and further research is needed to establish storage conditions which ensure prevention of fungal growth.
Keywords: Aflatoxins; Brown rice; Seasonal variation; Punjab; Pakistan